Conventional transarterial chemoembolization followed by irreversible electroporation for hepatocellular carcinoma - Meng Zhao; Fubao Li; Chuan Tian; Duo Cai; Congxiao Wang (BMC Cancer)
Abstract Objectives This study aimed to assess the effectiveness and safety of conventional transarterial chemoembolization (c-TACE) followed by irreversible electroporation (IRE) for the treatment of hepatocellular carcinoma (HCC). Methods From January 2019 to September 2019, 12 patients with HCC who received c-TACE followed by IRE comprised the study group. The control group comprised 15 patients who received c-TACE followed by radiofrequency ablation (RFA). The 1-month, 3-month, 6-month, and 12-month local control rates and median progression-free survival (PFS) were compared between the two groups. Additionally, postoperative complications were assessed. Results The study group comprised 12 patients (median age: 57.5 years; range: 46–68 years), while the control group consisted of 15 patients (median age: 56 years; range: 31–69 years). Local control rates at 1, 3, 6, and 12 months were 91.7%, 91.7%, 83.3%, and 33.3%, respectively, for the study group, and 73.3%, 66.7%, 66.7%, and 20.0% for the control group. Statistical analysis revealed no significant differences between the two groups. In terms of survival, 9 patients (75%) in the study group and 11 patients (73.3%) in the control group were still alive at the last follow-up. The median PFS was 8 months in the study group and 7 months in the control group, with no significant difference between the two groups (p = 0.96). Notably, no severe surgery-related side effects were observed in either group, and also no significant differences were found in postoperative complications between the two groups (p = 0.64). Conclusions The long-term therapeutic outcomes of c-TACE followed by IRE were found to be similar to those of c-TACE followed by RFA in the study. The research suggests that c-TACE followed by IRE offered an effective and safe treatment option for HCC.